2017
DOI: 10.1080/10428194.2017.1324157
|View full text |Cite
|
Sign up to set email alerts
|

High expression of INHBA is an adverse prognostic factor forde novoacute myeloid leukemia

Abstract: Inhibin-β A (INHBA) is a ligand of the transforming growth factor β superfamily and associated with tumorigenesis and tumor progression in solid tumors. In this study, we investigated the expression levels and clinical significance of INHBA in acute myeloid leukemia (AML). The results showed that high expression of INHBA was significantly correlated with elderly age (>60 years) (p = .038), adverse cytogenetic risks (p = .034), negative NPM1 mutation (p = .016), positive FLT3 internal tandem duplications (p = .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Activin A was reported to cause apoptosis of myeloma cells and chronic myeloid leukemia cells (10,11). On the other hand, similar to our results, high expression of βA subunit, which composes activin A, is an adverse prognostic factor for acute myeloid leukemia (12). Considering that activin A can affect tumor progression in an indirect manner, such as inhibiting anti-tumor immunity or attracting macrophages that helps tumor development (4,13), our results and the previous report suggest that activin A may be associated with progression of some other hematological malignancies in addition to MF/SS.…”
Section: Discussionsupporting
confidence: 90%
“…Activin A was reported to cause apoptosis of myeloma cells and chronic myeloid leukemia cells (10,11). On the other hand, similar to our results, high expression of βA subunit, which composes activin A, is an adverse prognostic factor for acute myeloid leukemia (12). Considering that activin A can affect tumor progression in an indirect manner, such as inhibiting anti-tumor immunity or attracting macrophages that helps tumor development (4,13), our results and the previous report suggest that activin A may be associated with progression of some other hematological malignancies in addition to MF/SS.…”
Section: Discussionsupporting
confidence: 90%
“…As an important member of the TGF-β, INHBA is associated with tumorigenesis and tumor progression in multiple types of solid tumors. Si et al found that high expression of INHBA is an adverse prognostic factor for de novo acute myeloid leukemia [60] . Wamsley et al demonstrates that INHBA mRNA and protein expression are elevated in human non-small cell lung cancer (NSCLC) and INHBA is a critical autocrine factor that matains mesenchymal properties of cancer-initiating cells in NSCLC [61] .…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [16] reported that RNAi could inhibit virus production and effectively inhibit pre-and/or post-integration infection events in the HIV-1 life cycle. Si et al [4] study showed that the H460 cells at 70% confluence was transfected using the optimal small interfering (siRNA) and the INHBA knockdown efficiency was 93% by the quantitative RT-PCR and the concentration of INHBAtargeting siRNA reduced 6% after 96 h of transfection. However, in the study, we constructed four inducible INHBA expression vectors as the experiment groups contain I-1, I-2, I-3, I-4, and an empty vector PLLU2G as the negative control group.…”
Section: Discussionmentioning
confidence: 99%
“…Activins are formed by the heterodimeric combinations of the two subunits (activin A =βA-βA, activin AB =βA-βB and activin B =βB-βB) [3] . Inhibin inhibits FSH secretion from the anterior pituitary and in turn regulates gonadal function and development [4] . And the mutations of INHBA gene effects on litter size in sheep significantly [5] , and plasma inhibin concentrations was related to higher ovulation rates in pigs during follicular phase [6] .…”
Section: Introductionmentioning
confidence: 99%